Stories and hermeneusis of the Silera woman - Contreras Jáuregui, Magda Milena; Celis Parra, Diana Milena; Velandia, Diana María; Yáñez Serrano, Carlos Alberto; Jaimes, Ruby Socorro (Sello Editorial Unipamplona, 2025)
The experience of generating stories about women does not seem to be an object of research that is developed with great interest or frequency, because it seems to entail meanings that alter certain established paradigms. Those that have dominated women through exercises of power, segregation, marginalization, domination, control, submission, and dependence. Realities that are reflected as part of the status quo and that, until now, seem to be considered a "sujets honteux." In this sense, a book dedicated to the women of Santo Domingo de Silos refers to the scant or nonexistent honor accorded them. Therefore, it is considered that they deserve recognition as part of a social issue that needs to be understood and interpreted through the telling of their life stories. Telling stories is about encountering consciousness to give meaning to some image. Women have not been considered historical subjects by historiographical science until relatively recent times; consequently, they have not been objects of knowledge worthy of mention.